The Job Sectors That Affecting the Employment Rate of Disabled People in Asia and Pacific Countries - Sutikno, Bayu (The Center for Disability Studies and Services Brawijaya University, 2018)
Disabled people certainly have a same opportunity to pursue their career life through working in the certain job sector that is suitable based on their abilities and skills. Employment rate of disabled people expresses the percentage number of disabled people who have successfully been producing the salary income. Therefore, this study aimed to identify the significant job sector that could give the real influence to the employment rate of disabled people in order to they know the appropriate job sector. Those job sectors were determined by applying the multiple linier regression equation with classical assumption test. Anyway, the data in this study was adopted from United Nations publication for employment rate of disabled people in Asia and Pacific countries 2015. The result showed that services and industries sector have the positive significant impact to the employment rate of disabled people with the adjusted coefficient determination value reveals to 85 %.